PARTISIPASI MASYARAKAT GAMPONG NUSA TERHADAP PENGELOLAAN SAMPAH DENGAN PROGRAM 3R - Farizah Hanum; Suhendrayatna Suhendrayatna; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The problem of garbage has become a problem together and must be done in special handling. The 3R program is one of the best ways to handle the waste problem in Gampong Nusa Kecamatan Lhoknga, Aceh Besar District. The purpose of this study is to assess the level of community participation in the waste management system of 3R in Gampong Nusa. Data collection is done by observation, questionnaire, interview, and documentation. The sample selection was chosen by random sampling technique based on Slovin equation with an error rate of 10%. The questionnaire used a Likert scale and analyzed by percentage formula. Reliability test carried out with the formula Flanagan, obtained value of 0.996 with reliable conclusions and very high category. Validity test done with Pearson product-moment obtained 100% valid instrument results. The results showed that the participation of the community of Gampong Nusa towards the 3R program activity was good. It means that the community actively participated in the handling of waste with 3R. It can be seen from the result of data analysis found that average of community participation reach 77,30% society strongly agree there is a program of 3R, 16,19% agree and only 5,79% less agree.